An implication of Fuzzy ANOVA: Metal uptake and transport by corn grown on a contaminated soil - Parchami, Abbas; Ivani, Reyhane; Mashinchi, Mashaallah; Kaya, Ihsan (ELSEVIER SCIENCE BV, 2017)
Three organic fertilizers of manure sheep, sewage sludge and municipal waste were mixed with soil at the rates of 0%, 1.25% and 2.5% (w/w), respectively. In a greenhouse experiment, corn seed were grown on pots of 3 kg treated contaminated soils and irrigated. Sixty days after sowing, the aerial plant parts were harvested and analyzed for Cadmium (Cd) and Lead (Pb) contents. Since all of data in this research are fuzzy, we need an extended version of analysis of variance (ANOVA) to investigate on these fuzzy observations. In this paper, as a method to compare several populations, the fuzzy analysis of variance (FANOVA) has been used where the collected data considered fuzzy rather than crisp numbers and therefore all calculations are based on FANOVA method. Although, ANOVA based on vague data can lead to a fuzzy decision, but measuring the vagueness of this fuzzy decision is one of advantages of proposed method from the applied point of view.
Keywords: Fuzzy numbers; Fuzzy statistics; Fuzzy analysis of variance; Organic fertilizers; Cadmium and Lead; CADMIUM AVAILABILITY; CONTROL CHARTS; SAMPLE-SIZE; VARIANCE; COPPER; ZINC; MANGANESE; RISK; LEAD; Automation & Control Systems; Chemistry; Computer Science; Instruments & Instrumentation; Mathematics